As marcas da transposição do Rio São Francisco: acesso à água, conflitos socioambientais e desenvolvimento no município de São José de Piranhas-PB - Sousa, Maria de Fátima Oliveira de (2020)
Water is an essential element to ensure quality of life and also the development of socioeconomic activities, consequently, its lack causes situations of conflict and vulnerability. In semi-arid regions, such as much of northeastern Brazil, shortage problems are a major challenge for which government interventions and policies are needed. The construction of large water works is one of the options widely adopted by these policies aimed at addressing supply needs, but the installation of these buildings brings with it a number of conflicting issues. One of these issues lies in the territorial restructuring caused by the removal of settlement nuclei from the places to be submerged. We will deal here with the São Francisco River Integration Project (PISF) as an integral strategy of the National Public Policy on Water Resources and structure designed to guarantee water supply to 12 million people in 390 municipalities in the Brazilian semiarid territory. Although the project is anchored in a strong appeal of "solving" the problems of water scarcity in the region considered as the polygon of droughts in the Northeast, the grandeur of the work also produces numerous controversies and conflicts. Along its 477 kilometers long, transposition produced different marks as it redefined territories, identities, symbols and social relationships. As locus of analysis we chose the municipality of São José de Piranhas, Paraíba. The choice is justified by this municipality having proportionally the highest percentage of territorial expropriation of the entire course of the transposition work, more than 5,200 hectares, 7.76 % of rural area Piranhense as stated in the Environmental Impact Report - RIMA (2004). Interestingly, Saint Joseph of Piranhas had already gone through a similar process in 1932 when the seat of the municipality, as well as much of its territorial extension, was flooded giving way to the construction of the Avid Engineer reservoir, responsible for capturing water that supplies different cities in the upper sertão of Paraiba. The aim of this study is to identify which social, cultural and political changes were engendered by the process of deterritorialization and reterritorialization in the Cacaré and Riacho de Boa Vista communities in São José de Piranhas in Paraíba during the São Francisco River transposition project. The study involved bibliographic, documentary and field research where open or semi-structured interviews were conducted, and interviews with focus groups. In order to bring the interpretations of different actors and entities that made up the scenario analyzed, we sought as respondents: representatives of the Ministry of Integration, members of the Rural Workers Union of São José de Piranhas; focus groups in the associations of residents of the Rural Productive Villages (Cacaré and Irapuá ) and several families residing in these localities. We used as a methodological basis the political ecology and cosmography of Little (2006/2002) in addition to the concepts of space, place, territory, deterritorialization and reterritorialization references, Little (2002) and Haesbaert (2004). The instability caused by the displacement of communities, the departure of families from their places of origin and the disruption of affective bonds are some of the greatest difficulties faced. Among the new social dynamics provided by the context of deterritorialization is the conquest of the land by those who were previously in the condition of residents or middlemen.